Analysis of landing performance and ankle injury in elite British artistic gymnastics using a modified drop land task: A longitudinal observational study - Glynn, B.; Laird, J.; Herrington, L.; Rushton, A.; Heneghan, N. R. (Physical Therapy in Sport, 2022)
Objectives To determine whether differences in landing force and asymmetry of landing force exist between gymnasts at the time of data collection versus those that subsequently experienced an ankle injury 12-months later.